Pengolahan dan Manajemen Usaha Produk Camilan Keripik Ikan Mujair dalam Upaya Meningkatkan Potensi Lokal - Ziecky Mardoni (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
The purpose of the Community Service Program for the Utilization of Science and Technology for the Community of Solok City, Kel IX Korong, is to provide training and assistance on processing and business management to the "Mujair IX Korong" Fish Farming Partner Group which produces processed Mujair fish. Because all this time, what partners have done for tilapia fish products are only selling tilapia fish products directly without further processing. For this reason, in an effort to increase local potential, it is necessary to provide counseling to partners. Based on this, the Community Service Program for the Utilization of Science and Technology for the Community of Solok City, IX Korong Village, for partners to increase knowledge and skills in processing tilapia fish through training and assistance in making processed tilapia fish products, financial management for their efforts and providing knowledge and enlightenment. in strategic management in marketing products with an online system. From the results of this counseling, it was found that the productivity produced by partners in processing tilapia fish into chips snack products began to increase in sales. The marketing network that is carried out is increasingly widespread. Thus, the local potential generated by the “Mujair XI Korong” Fish Farming Partner Group will increase.